The political position - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
As local consumer tastes for wheat-based products in food-deficit countries have been developed, prices have often been kept artificially low by governments and subsidies provided by producer-exporters. The United States government subsidized its...